FORECASTING THE INFLATION IN THE REPUBLIC OF NORTH MACEDONIA BY USING ARIMA MODEL - Josimovska Nikolov, Ana; Gegovska-Zajkova, Sonja (Matematichki Bilten, 2024)
Modeling and forecasting inflation play a critical role in the economic management of all countries, particularly developing ones. This paper is focused on predicting inflation in the Republic of North Macedonia. The selected method for econometric inflation modeling is the Box-Jenkins approach, utilizing an ARIMA model. The analyzed time series focuses on the consumer price index (CPI), based on 2010 as the reference year. It encompasses 249 observations, with a monthly frequency, spanning from January 2002 to September 2022. The analysis demonstrates that the model accurately forecasts inflation for the initial two months beyond the sample period, with a mere 0.1 and 0.5 percentage point disparity between the actual and predicted inflation rates, respectively. Consequently, it can be affirmed that the Box-Jenkins methodology provides highly precise inflation forecasts for the Republic of North Macedonia, particularly within the first two months beyond the sample period of the time series.